Attentional mechanisms of social perception are biased in social phobia - Boll, Sabrina (Journal of anxiety disorders, 2016)
Previous studies of social phobia have reported an increased vigilance to social threat cues but also an avoidance of socially relevant stimuli such as eye gaze. The primary aim of this study was to examine attentional mechanisms relevant for perceiving social cues by means of abnormalities in scanning of facial features in patients with social phobia. In two novel experimental paradigms, patients with social phobia and healthy controls matched on age, gender and education were compared regarding their gazing behavior towards facial cues. The first experiment was an emotion classification paradigm which allowed for differentiating reflexive attentional shifts from sustained attention towards diagnostically relevant facial features. In the second experiment, attentional orienting by gaze direction was assessed in a gaze-cueing paradigm in which non-predictive gaze cues shifted attention towards or away from subsequently presented targets. We found that patients as compared to controls reflexively oriented their attention more frequently towards the eyes of emotional faces in the emotion classification paradigm. This initial hypervigilance for the eye region was observed at very early attentional stages when faces were presented for 150ms, and persisted when facial stimuli were shown for 3s. Moreover, a delayed attentional orienting into the direction of eye gaze was observed in individuals with social phobia suggesting a differential time course of eye gaze processing in patients and controls. Our findings suggest that basic mechanisms of early attentional exploration of social cues are biased in social phobia and might contribute to the development and maintenance of the disorder.
Gesehen am 17.09.2019